2022
DOI: 10.3389/fevo.2022.884159
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Engineered Sex Ratio Distortion in Insects

Abstract: Insects have evolved highly diverse genetic sex-determination mechanisms and a relatively balanced male to female sex ratio is generally expected. However, selection may shift the optimal sex ratio while meiotic drive and endosymbiont manipulation can result in sex ratio distortion (SRD). Recent advances in sex chromosome genomics and CRISPR/Cas9-mediated genome editing brought significant insights into the molecular regulators of sex determination in an increasing number of insects and provided new ways to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…Such male-killing factors are known in several Dipteran species 37 (e.g. the Nix sex-determining factor), and they have a potential of use in a pest management 38 . These factors for the CPB have not been reported, however, considering the observed segregation ratios in the experimental progenies, two hypothetical models of the primary sex ratio modification arise.…”
Section: Discussionmentioning
confidence: 99%
“…Such male-killing factors are known in several Dipteran species 37 (e.g. the Nix sex-determining factor), and they have a potential of use in a pest management 38 . These factors for the CPB have not been reported, however, considering the observed segregation ratios in the experimental progenies, two hypothetical models of the primary sex ratio modification arise.…”
Section: Discussionmentioning
confidence: 99%
“…The assembly was scaffolded using Bionano optical and physical maps [ 41 ], followed by Hi-C [ 20 ]. Hi-C analysis was performed based on 0.5 Gb raw data from the Hi-C libraries, from which 0.32 G (64.7%) were unique.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis result of the two treatments showed that the calculated chi-square value was lower than the table chi-square value so, Fisher theory determined that the sex ratio of male and female being 1:1 was acceptable (Table 2). The sex ratio is the relative number of male and female in a population which is shown by the comparison of the number of male with 100 female (Compton and Tu 2022). BPH age distribution from the first egg hatched until the end of observation was calculated based on the total number of hatched eggs and the total number of eggs placed, which can be seen in Figure 5.…”
Section: Resultsmentioning
confidence: 99%